An Analysis of Iraqi EFL Fifth Preparatory Pupils Feedback Discourse Interaction - Mohammed Abbas Alkhateeb , Muna; Zeid Jawad Hassan Watoot, Sebe; Ali Nayif Hasan, Abd (مجلة كلية التربية, 2020)
Student-teacher language interaction is given a great environment through classrooms.  Previously students had no role in the teaching-learning process, while teachers were the corner stone of the class. Nowadays studies show that students control classes verbally where they lead the talk more than teachers. Student-teacher interaction is expected to be encouraged by teachers, providing not only student-teacher interaction but also student-student interaction in the form of groups or pairs or through assignments or presentations. There has been a great shift in the concept of the process of classroom and interaction. More emphasis is given to language learning as a result of classroom interaction. Changing from silent recipients to active participants in the learning process, learners play an active role in the whole classroom process and subsidize greatly to the language learning process. The study aims at interpreting the learners' interact. This study is limited to the analysis of Iraqi EFL fifth preparatory students when interacting inside their classes. The data chosen to analyze is the transcribed interaction inside the class. It is concluded that pronouns are used by the participants for the purpose of defining roles and providing overt directions. This is made more specific through the use of modals of necessity. Direct imperatives are also used by all the participants but in different degrees.